“The Saint Phenomenon” among Anthropological Conditions of the Religious Faith - Parzych-Blakiewicz, Katarzyna (Paedagogia Christiana, 2016)
The author discusses “the saint phenomenon” as an element in the extension of the religious faith. According to the biblical message, God seeks human beings, which leads to a meeting. From the perspective of human, the religious faith is a condition for this meeting. We talk about the religious faith as the virtue or charisma. The virtue ministers to the salvation, and also leads to the personal meeting with God. The charisma qualifies a person to working for the ecclesial community. The religious faith develops in a “human” milieu consisting of the community, educational activities, and personal religious life. The saints belong to the human milieu of faith, as heroes of Christian virtues and teachers of faith, and also miracle workers. The beatification or canonization points to the charisma of faith of the deceased Christian believer. “The saint phenomenon” expresses the Christian ethos and the precedence of the eternity to the temporal life. It also means the existence of relationships between the living human and the late.